Distribution of HPV Types in Tumor Tissue from Non-Vaccinated Women with Cervical Cancer in Norway - Sveinung Wergeland Sørbye; Bente Marie Falang; Mona Antonsen (MDPI AG, 2023)
Background: Understanding the distribution of HPV types in cervical cancer cases is crucial for evaluating the effectiveness of HPV screening and vaccination in reducing cervical cancer burden. This study aimed to assess genotype prevalence in the pre-vaccine era among 178 cervical cancer cases detected during a 20-year screening period in Northern Norway and compare the potential efficacy of HPV vaccines in preventing cervical cancer. Methods: A total of 181 formalin-fixed paraffin-embedded (FFPE) tissue samples from non-vaccinated women diagnosed with cervical cancer between 1995 and 2015 in Troms and Finnmark, Norway, were analyzed using a 45-type HPV DNA test. The results were compared to a 7-type HPV mRNA test targeting oncogenic types included in the nonavalent HPV vaccine. Results: Invalid HPV test results were observed in 1.7% (3/181) of the samples and were subsequently excluded from further analysis. Among the remaining cases, 92.7% (165/178) tested positive for HPV using any test combination. HPV DNA was detected in 159 cases (89.3%), while HPV mRNA was detected in 149 cases (83.7%). The most prevalent HPV types were 16 and 18, responsible for 70.8% of the cases, with the nonavalent vaccine types accounting for 86.6% of cases. HPV 35 was identified in eight cases (4.5%). Conclusion: The bivalent/quadrivalent HPV vaccines have the potential to prevent 76.4% (126/165) of HPV-positive cervical cancer cases, while the nonavalent vaccine could prevent 93.3% (154/165) of cases. Tailoring screening strategies to target HPV types with the highest oncogenic potential may improve cervical cancer detection and enable targeted interventions for high-risk individuals. The use of a 7-type HPV mRNA test holds promise as an advantageous approach.